Ferrospintronic Order in Noncentrosymmetric Antiferromagnets: An Avenue Toward Spintronic-Based Computing, Data Storage, and Energy Harvesting - Allende-Prieto, S (John Wiley and Sons Inc, 2025)
A ferroic order, ferrospintronic (FSp) order, arising in some magnetic materials lacking inversion symmetry is reported on. Emerging from a macroscopic spontaneous symmetry breaking of both the time reversal T and the spatial inversion, while maintaining the symmetry, the order parameter is given by the dipolar moment of the spin density (Formula presented.). Herein a model is advanced that fulfills the symmetry requirements mentioned earlier and its properties are investigated. With the aid of a mean-field theory, its stability against thermal fluctuations is studied and evidence of truly ferroic states that result from breaking its symmetry is provided. Three predictions that can be checked experimentally to distinguish this class of materials from other compounds are provided. In the first place, it is illustrated that FSp systems host the potential for multiferroic behavior. Second, it is shown that the generic FSp system responds under strain by generating spin currents that can be used in spintronic devices, therefore showing a piezospintronic effect. Finally, it is proven that domain walls in the FSp order parameter lead to magnetoresistive effects. All of the findings mentioned earlier are a significant breakthrough in spintronics and multiferroic phenomena and they have wide-ranging implications for advancing materials and technologies, particularly in computing and energy harvesting. © 2024 Wiley-VCH GmbH.